The Biomarkers for Predicting Viral HepatitisAssociated Hepatocellular Carcinoma - Yang, Qing; Sun, Changfeng; Sheng, Yunjian; Chen, Wen; Deng, Cunliang (Turkish Journal of Gastroenterology, 2022)
Background: Hepatocellular carcinoma (HCC) is the fifth most common cancer in the world, and more than half of the newly diagnosed cases are chronic hepatitis B patients. Due to the lack of specific clinical manifestations, many patients are already at an advanced stage at the time of diagnosis and therefore have missed the best time for treatment. Organs in a pathological state usually secrete specific substances into the blood, which can indirectly indicate the pathological state of the organ, so some biological markers in the blood can be used as a tool to predict the incidence of HCC. Methods: The Research articles related to HCC were collected by searching PubMed databases with the keywords “hepatocellular carcinoma”, “serum biomarker”, “hepatitis B”, “prediction” and “prognosis”, and Additional articles were identified by manual search of references found in the primary articles, followed by a summary and review. Results: Viral hepatitis is the main cause of HCC worldwide, and this phenomenon is particularly prominent in Asian and African populations. A variety of serological markers including M2BPGi, IL-6 and COMP can be used to predict the incidence of long-term HCC in patients. The risk of HCC is dynamic rather than constant, and dynamic detection will help improve prediction accuracy. For hepatitis B patients, HBV DNA load and HBcr Ag are important predictive markers of HCC. Conclusion: For a high-risk population of HCC, early risk prediction is helpful to guide clinical work, and timely adjustments of the screening frequency and treatment plan are helpful to prolong the survival time of HCC patients.